2023
DOI: 10.1038/s41598-023-40378-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the inclusion of extruded flaxseed in the diet of fattening pigs on lipid metabolism and tissue redox status

Abstract: The aim of the study was to evaluate the effect of a diet containing extruded flaxseed (Linum usitatissimum L.) on the fatty acid composition of the loin, blood lipid parameters, and the redox status of tissues of finishing pigs. A total of 160 weaners (about 30–110 kg BW) were assigned to four experimental groups of 40 animals each (5 replicates with 8 individuals each). Group C (control) received a diet in which the fat source was soybean oil, while in groups 2FE, 4FE and 6FE soybean meal was replaced with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…In the first part of the research, published by Klimiuk et al [ 11 ] and Czech et al [ 16 ], animals in experimental groups were given diets with 2%, 4%, or 6% extruded flaxseed instead of barley. It was demonstrated that the addition of 4% extruded flaxseed proved to be the most promising solution for addressing the deficiency of polyunsaturated fatty acids in diets for fattening pigs.…”
Section: Discussionmentioning
confidence: 99%
“…In the first part of the research, published by Klimiuk et al [ 11 ] and Czech et al [ 16 ], animals in experimental groups were given diets with 2%, 4%, or 6% extruded flaxseed instead of barley. It was demonstrated that the addition of 4% extruded flaxseed proved to be the most promising solution for addressing the deficiency of polyunsaturated fatty acids in diets for fattening pigs.…”
Section: Discussionmentioning
confidence: 99%